Analisis Pengaruh Kualitas Aplikasi Employee Self Service (EES) Terhadap Kepuasan Kerja Dan Efektivitas Kinerja Karyawan - Dodi Setiawan Riatmaja; Dinda Sukmaningrum; Narwanto Nurcahyo; Lalu Supardin (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
During the Fourth Industrial Revolution, technological advancements are growing at an accelerating pace. In this new era, technology and personalization have become critical concerns for digital startups. This research aims to analyze the impact of Employee Self-Service (ESS) implementation quality on job satisfaction and employee productivity. A quantitative method is employed in this study. The primary source of information for this investigation is employees working at digital startups in Yogyakarta. A total of 130 participants are sampled for this research, and the analysis is conducted using Smart PLS software for Partial Least Squares analysis.The participants in this study are employees of digital startups in Yogyakarta. Based on the results of this research project, the quality of ESS implementation in digital startups in Yogyakarta has a significantly positive impact on both job satisfaction and employee productivity.